A systematic review of randomized controlled trial characteristics for interventions to improve upper extremity motor recovery post stroke. Issue 4 (19th May 2023) - Saikaley, Marcus; McIntyre, Amanda; Pauli, Griffin; Teasell, Robert
ABSTRACT: Introduction: Given the prevalence of motor deficits post-stroke, a large proportion of stroke rehabilitation interventions are directed toward motor recovery. Objectives: The purpose of this study is to present a detailed investigation of the methodological characteristics in the stroke rehabilitation literature with respect to randomized controlled trials (RCTs) designed to facilitate upper extremity motor recovery. Methods: This review was conducted following guidelines from the Preferred Reporting Items for Systematic reviews and Meta Analyses (PRISMA) statement. English articles of RCTs were eligible if they were published before April 1, 2021 and applied an intervention to the hemiparetic upper extremity of individuals post stroke as the primary objective of the study, or recorded at least one upper extremity related outcome measure. Results: The number of RCTs for upper extremity rehabilitation interventions post stroke has been increasing, with over three quarters of RCTs published in the last decade. In total, 1, 307 RCTs met inclusion criteria for which the mean sample size (start/finish) was 45.8 (SD 55.4)/41.8 (SD 49.7). The median sample size (start/finish) was 30 (IQR 20–48)/29 (IQR 19–44). The mean PEDro score was 6.12 (SD 1.55). 251 RCTs (19%) were multi-centered trials. Key methodological measures of quality remain low including the blinding of assessors (59%), intention to treat analyses (42%) and concealed allocation (37%). Conclusions: There is a large number of RCTs evaluating stroke rehabilitation upper extremity interventions. Research quality continues to be a challenge (low percentage of key quality indicators, small percentage of multicentred trials, small sample sizes) but is slowly improving.